Structural Elucidation of Heteropolysaccharides from the Peach-Shaped Dictyophora indusiata and Its Anti-Inflammatory Activity - Ying He; Hao Yang; Yaxin Liu; Yanting Sun; Zeguo Feng; Xueying Zheng; Fei Wang; Lei Ma; Jianbao Zhang; Dan Xu; Hui Guo; Liguo Qin; et al. (Foods)
Dictyophora indusiata is commonly utilized as a functional food in China and other Asian countries. The peach-shaped phase of this fungus is nutritionally and taste-wise similar to its mature fruiting bodies. However, there is limited research on the polysaccharides found in the peach-shaped D. indusiata. A heteropolysaccharide was extracted from the volva of peach-shaped D. indusiata (DIVP). Analyses using high-performance gel permeation chromatography, methylation and NMR revealed that DIVP comprises glucose, glucuronic acid, galactose, and mannose. Its structure features a backbone that consists of →3)-β-D-Glcp-(1→ units with branches at →4)-β-D-Glcp-(1→, →6)-α-D-Galp-(1→ and terminal α-Manp-(1→ residues. Physicochemical assessments including X-ray diffraction, thermal, zeta potential and viscosity characterization indicated that DIVP is a semi-crystalline polymer exhibiting excellent physical and thermal stability. Cytokine antibody array and proteome profiler human phosphokinase analyses demonstrated that DIVP downregulates the expression levels of cytokines and alters the phosphorylation status of 16 proteins in human U937 macrophages induced by lipopolysaccharides, indicating its anti-inflammatory activity. These findings suggest that the polysaccharide from the volva of peach-shaped D. indusiata is primarily composed of β-1,3-glucan, which exhibits stable physicochemical properties and anti-inflammatory activity, providing a foundation for its potential use as an anti-inflammatory agent or functional food.